Evaluation of cytotoxic effects and acute and chronic toxicity of aqueous extract of the seeds of Calycotome villosa (Poiret) Link (subsp. intermedia) in rodents - Badiaa Lyoussi; Khadija Cherkaoui Tangi; Nicole Morel; Mohamed Haddad; Joelle leclercq (Mashhad University of Medical Sciences, 2018)
Objective: The present investigation was carried out to evaluate the safety of an aqueous extract of the seeds of Calycotome villosa (Poiret) Link (subsp. intermedia) by determining its cytotoxicity and potential toxicity after acute and sub-chronic administration in rodents. Materials and Methods: Cytotoxic activity was tested in cancer and non-cancer cell lines HeLa, Mel-5, HL-60 and 3T3. Acute toxicity tests were carried out in mice by a single oral administration of Calycotome seed-extract (0 - 12 g/kg) as well as intraperitoneal doses of 0 - 5 g/kg.  Sub-chronic studies were conducted in Wistar rats by administration of oral daily doses for up to 90 days. Changes in body and vital organ weights, mortality, haematology, clinical biochemistry and histologic morphology were evaluated. Results: The lyophilized aqueous extract of C. villosa exhibited a low cytotoxicity in all cell lines tested with an IC50 > 100 µg/ml. In the acute study in mice, intra-peritoneal administration caused dose-dependent adverse effects and mortality with an LD50 of 4.06 ± 0.01 g/kg.In the chronic tests, neither mortality nor visible signs of lethality was seen in rats. Even AST and ALT were not affected while a significant decrease in serum glucose levels, at 300 and 600 mg/kg was detected.  Histopathological examination of the kidney and liver did not show any alteration or inflammation at the end of treatment. Conclusion: In conclusion, the aqueous extract of C. villosa seed appeared to be non-toxic and did not produce mortality or clinically significant changes in the haematological and biochemical parameters in rats.